Risk factors for all-cause mortality during the COVID-19 pandemic compared with the pre-pandemic period in an adult population of Arkhangelsk, Russia - Ekaterina Krieger; Alexander V. Kudryavtsev; Ekaterina Sharashova; Olga Samodova; Vitaly A. Postoev (Scientific Reports)
Abstract We investigated and compared mortality rates and risk factors for pre-pandemic and pandemic all-cause mortality in a population-based cohort of men and women in Arkhangelsk, Russia. A prospective cohort study enrolled 2,324 participants aged 35 to 69 years between 2015 and 2017. All participants were followed up for all-cause deaths using the mortality registry. Mortality rates per 1000 person-years were calculated for men and women in the pre-pandemic and pandemic periods. Cox regression models were used to investigate demographic, lifestyle, and health characteristics associated with increased risk of death in both periods. During the pandemic, age-standardized all-cause mortality increased in women, but minor change was observed in men. Older age, smoking, and diabetes were associated with a higher risk of all-cause death in both periods and for both sexes. In women, higher risk during the pandemic was associated with obesity, angina, elevated cystatin C levels, and a history of COVID-19. In men, asthma and elevated hs-Troponin T levels increased the risk of death during the pandemic, while elevated hs-CRP and NT-proBNP levels were associated with higher risk in both periods. Targeted preventive interventions for men and women with specific risk factors can be implemented during potential future infectious disease outbreaks.